Social distance matters in dictator games: Evidence from 11 Mexican villages - Natalia Candelo; Catherine C. Eckel; Cathleen Johnson (Games, 2018)
We examine the impact of social distance in dictator game giving. The study is conducted in a field setting with high stakes (two days' wages). The sample is a representative sample from eleven low-income Mexican villages. Subjects make multiple dictator decisions simultaneously, in a comparative dictator game. We show the relationship between social distance and giving using several family members, a member of the same village, and a stranger from a different village. Dictator giving shows substantial variation across recipient types and varies directly with social distance. We find higher giving towards family members than towards community members and strangers. Furthermore, our results indicate that giving to community members and to strangers is not different. In light of our results, it is important to consider the impact of social distance on inter- and intra-household transfers in policy interventions that alleviate poverty, e.g., conditional transfers.
Keywords: 330; charitable giving; social distance; development; lab-in-field experiment; comparative dictator game